(untitled) (Journal of Geography and Environmental Management, 2016)
Glacier mapping using remote sensing techniques has become popular in the past decade. This paper presents a review of glacier mapping methods using remote sensing. It also highlights the advantages and problems of remote-sensing-based glacier mapping. In addition, our previous experience on glacier mapping method are provided.It is concluded that semi-automated mapping of clean glacier ice is faster, not generalized and generating reproducible results, i.e. the same threshold values always generate the same outlines. This method can be the best method for glacier mapping comparatively large area.